Ambiguous Antidotes : Virtue as Vaccine for Vice in Early Modern Spain - Kallendorf, Hilaire, 1974- (Book collections on Project MUSE., 2017)
In Ambiguous Antidotes, Hilaire Kallendorf explores the receptions of Virtues in the realm of moral philosophy and the artistic production it influenced during the Spanish Gold Age.